Phytochemistry and antibacterial activity of the methanol, petroleum ether and aqueous extracts of the leaves, stem bark and roots of bobgunnia fistuloides - E. Anwani, Samuel; B. Etsuyankpa, Muhammed; P.I. Ogah, Suleman.; K. Mensah, Peter (International Journal of Advanced Chemistry, 2021)
Ethno-medicinally, Bobgunnia fistuloides parts (leaves, bark and roots) have been used by the Nupe communities in Niger State, Nigeria to treat various diseases for decades. The phytochemical and antibacterial activity of the methanol, petroleum ether and aqueous extracts of the leaves, roots and stem bark of Bobgunnia fistuloides were investigated using standard methods. The leaves, roots and stem bark of Bobgunnia fistuloides plant were collected from Binin village, Gbako Local Government Area (LGA) in Niger State Nigeria. The antibacterial activities of the plant extracts were determined using 5 pathogenic bacteria (Staphylococcus aureus, Bacillus subtilis, Klebsiella pneumoneae, Salmonella typhi and Escherichia coli). The result of the phytochemicals, in mg/100 g, revealed the values of 479.73Â±0.20, 465.98Â±0.14, 482.77Â±0.17; 1.71Â±0.06, 25.14Â±0.02, 23.90Â±0.03; 29.09Â±0.20, 36.77Â±0.06, 24.79Â±0.14; 22.40Â±0.02, 25.14Â±0.02, 23.90Â±0.03; 577.29Â±0.24, 586.52Â±0.11, 230.19Â±0.03 respectively for the phenols, flavonoids, alkaloids, tannins and saponnins contents of the roots; leaves and stem bark of the plant. In this study, the saponnins and phenol contents of the plant parts were relatively higher than the other parameters investigated. The leaves were found to contain more active principles, followed by the roots and stem bark. Based on the antibacterial activities, the result revealed that the respective zones of inhibition of the growths of the test microorganisms, with the exception of the aqueous leaves extract (against Staphylococci aureus; 25.00Â±1.00 mm) recorded highest values for the petroleum ether extracts of the stem bark (32.67Â±0.58, 33.00Â±1.00, 31,67Â±0.58 and 35.10Â±1.00 mm for E. coli, B. subtilis, S. typhii and K. pneumonea respectively). Statistically, Klebsiella pneumoneae (17.13Â±0.00 mm) recorded the highest average zones of inhibition based on the susceptibility of the pathogens to the extracts, followed by Salmonella typhi (16.92Â±1.00mm). The least zone of inhibition (12.00Â±0.50 mm) was recorded for B. subtilis using the stem bark aqueous extract of the plant while the highest value was recorded for the petroleum stem bark extract against K. pneumonea (35.00Â±1.00 mm). The MIC and MBC of the extracts ranged from 12.50 to 100.00 mg/cm3 respectively. The phytochemical components and antibacterial activities of the plant extracts in this study support the therapeutic value and the ethno-medicinal applications of this plant by the Nupe communities of Niger State Nigeria.Â Â Â